Atrophic Dermatofibrosarcoma Protuberans with Eosinophilic Infiltration - Anber Mahboob; Claire Turgeon; Syeda Qasim; Arif Usmani (Dermatopathology, 2022)
Dermatofibrosarcoma protuberans (DFSP) is a rare, locally aggressive spindle cell mesenchymal tumor arising in the dermis, with low metastatic potential. The most commonly affected sites are the trunk and proximal extremities; rarely are acral sites involved. Atrophic DFSP is a rare form of DFSP, that is morphologically different but histologically similar to DFSP. It commonly affects young adults between the ages of 20 to 50 years. The current management strategy for atrophic DFSP is surgical excision with long-term follow-up to detect any recurrence. Only one known case of atrophic DFSP with eosinophilic infiltration is what makes our case an exceptionally rare presentation.